De novo Transcriptome Assembly of a Chinese Locoweed (Oxytropis ochrocephala) Species Provides Insights into Genes Associated with Drought, Salinity, and Cold Tolerance - He, Wei; Zhuang, Huihui; Fu, Yanping; Guo, Linwei; Guo, Bin; Guo, Lizhu; Zhang, Xiuhong; Wei, Yahui (Frontiers in Plant Science, 2015)
Background: Locoweeds (toxic Oxytropis and Astraglus species), containing the toxic agent swainsonine, pose serious threats to animal husbandry on grasslands in both China and the US. Some locoweeds have evolved adaptations in order to resist various stress conditions such as drought, salt and cold. As a result they replace other plants in their communities and become an ecological problem. Currently very limited genetic information of locoweeds is available and this hinders our understanding in the molecular basis of their environmental plasticity, and the interaction between locoweeds and their symbiotic swainsonine producing endophytes. Next-generation sequencing provides a means of obtaining transcriptomic sequences in a timely manner, which is particularly useful for non-model plants. In this study, we performed transcriptome sequencing of Oxytropis ochrocephala plants followed by a de nove assembly. Our primary aim was to provide an enriched pool of genetic sequences of an Oxytropis sp. for further locoweed research. Results: Transcriptomes of four different O. ochrocephala samples, from control (CK) plants, and those that had experienced either drought (20% PEG), salt (150 mM NaCl) or cold (4 °C) stress were sequenced using an Illumina Hiseq 2000 platform. From 232,209,506 clean reads 23,220,950,600 (~23 G nucleotides), 182,430 transcripts and 88,942 unigenes were retrieved, with an N50 value of 1,237. Differential expression analysis revealed putative genes encoding heat shock proteins (HSPs) and late embryogenesis abundant (LEA) proteins, enzymes in secondary metabolite and plant hormone biosyntheses, and transcription factors which are involved in stress tolerance in O. ochrocephala. In order to validate our sequencing results, we further analyzed the expression profiles of nine genes by quantitative real-time PCR. Finally, we discuss the possible mechanism of O. ochrocephala’s adaptations to stress environment. Conclusion: Our transcriptome sequencing data present useful genetic information of a locoweed species. This genetic information will underpin further research in elucidating the environmental acclimation mechanism in locoweeds and the endophyte-plant association.